Synthetic glycoprotein D-related peptides protect mice against herpes simplex virus challenge. - Eisenberg, R J (1985)
Glycoprotein D (gD) of herpes simplex virus (HSV) protects mice from a lethal challenge by either HSV type 1 (HSV-1; oral) or HSV-2 (genital). We evaluated whether synthetic peptides representing residues 1 through 23 of gD (mature protein) can be used as a potential synthetic herpesvirus vaccine. The immunogenicity of the peptides was demonstrated by the biological reactivity of antipeptide sera in immunoprecipitation and neutralization assays. All sera which immunoprecipitated gD had neutralizing against both HSV-1 and HSV-2. The highest titers were found in animals immunized with the longest peptides. The region of residues 1 through 23 was immunogenic regardless of whether the type 1 or type 2 sequence was presented to the animal. Immunization of mice with gD or synthetic peptides conferred solid protection against a footpad challenge with HSV-2. However, the peptides were not as effective as gD in protection against an intraperitoneal challenge. The results suggested that synthetic vaccines based on gD show promise and should be more rigorously tested in a variety of animal models.